MYSTICAL-METAPHYSICS: THE TYPE OF ISLAMIC PHILOSOPHY IN NUSANTARA IN THE 17th-18th CENTURY - Humaidi Humaidi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article is aimed to analyze the geneology of the origin of philosophical thinking of scientists in Nusantara, especially the one which developed in the seventeenth and the eighteenth century, also included the themes which developed in those periods as disscussion material, the object of analyzes and debate. The history of Islamic entered in Nusantara more decribed with Islamic type which demansioned mysticism. This theses is based on the Islamic capacity which united the tradition and Nusantara culture which have the same background as Islamic mysticism, especially in Hindu and Budha. Only a few mentioned that Islam in Indonesia has the type of philosophical rational. The implication of this view is only a bit of the researches connected with Islam with rationally philosophical elemension. Based on the result of the writer’s investigation about the works of Islamic scientists in Nusantara like Hamzah Fansurî, Syams al-Dîn al-Sumatranî, Nûr al-Dîn al-Ranirî, Muhammad Yûsuf al-Maqassarî, ‘Abd al-Ra’ûf al-Sinkilî, ‘Abd al-Samad al-Palimbanî, and Muhammad Nafis al-Banjari indicates that their thinking and arguments are very rational. Their work have colorize the type of thinking of Islamic Philosophy in Nusantara which have developed since the seventeenth century even they have been started since the sixteenth century